Mom, dad, put down your phone and talk to me: how parental phubbing influences problematic internet use among adolescents - Saifang Liu; Peiqian Wu; Xiaoxi Han; Mengyun Wang; Yuecui Kan; Kuiyuan Qin; Jijun Lan (BMC Psychology, 2024)
Abstract Background The positive association of parental phubbing with internalising and externalising problems among adolescents has gained academic traction. To date, limited research has investigated the association of parental phubbing and adolescents’ Problematic Internet Use (PIU). Furthermore, the mechanism underlying this association is largely unknown. These gaps limit our understanding of family-related issues affecting PIU among adolescents. The present study explores whether there is a relation between parental phubbing and PIU and investigates the mechanisms underlying this relation among adolescents. Methods The participants were 495 junior high schoolers aged 11–15 years. Participants completed questionnaires on their experiences with PIU, parental phubbing, parent–child relationships, and basic psychological needs satisfaction. Results The results showed a direct and indirect positive association between parental phubbing and PIU. Furthermore, parental phubbing indirectly influenced PIU and was mediated by the parent–child relationship and basic psychological needs satisfaction, respectively. Moreover, the parent–child relationship and basic psychological needs satisfaction were sequentially mediated. Conclusions Our study highlights the crucial role of parents in the development of adolescent PIU and provides theoretical and practical guidelines for PIU prevention and intervention.